Effect of the Physical Environment on the Health-related Quality of Life of the Low-income Korean Elderly Population - Seonhye LEE; Chang Heon CHEONG (Tehran University of Medical Sciences, 2018)
Background: The increasing number of elderly citizens due to changes in the social structure is of national interest. This study aimed to provide basic data for devising policies to promote the quality of life of elderly National Basic Livelihood Security System (NBLSS) beneficiaries in South Korea by identifying the effects of their general characteristics and physical environment on their health-related quality of life (HRQoL). Methods: Using the 2013 Korean Community Health Survey (KCHS) raw data, we analyzed 3537 NBLSS beneficiaries aged 65 yr and older. HRQoL was measured using the Euro QoL five-dimension questionnaire (EQ-5D). Hierarchical multiple regression analyses were used to predict the EQ-5D scores. Results: The explanatory power for HRQoL increased to 21.4% when the general characteristics and physical environment were included. HRQoL showed statistically significant differences in the environmental variable, level of safety (P=0.001), natural environment (P=0.001), living environment (P=0.001), traffic condition (P<0.001), and access to health services (P<0.001). Physical environment positively correlated with HRQoL(r=.119, P<0.001), thus confirming its influence (ß=.092, P<0.001). Conclusion: We should strive to manage the physical environment to improve the quality of life of elderly NBLSS beneficiaries.